Self-efficacy, locus of control and attitude among engineering students: appreciating the role of affects in learning efforts - Alias, Maizam; Akasah, Zainal Abidin; Kesot, Mohd Jahaya (Elsevier Science Ltd, 2012)
Ignoring the contribution of the affective dimension of learning (such as attitudes) with an over emphasis on the cognitive aspect of learning are no longer adequate in providing sustainable engineering education. In this study, three psychological attributes related to the affective dimension of learning (locus of control, self-efficacy and attitude towards engineering studies) were investigated using a descriptive design method. The preliminary results involving a group of 60 diploma civil engineering students indicate that most students tend to have internal locus of control rather than external locus of control; above average level in self-efficacy and positive attitudes towards engineering with female students having stronger positive attitude compared to male students.